Manajemen Resiko Bank Wakaf - Syuhada Fela Yudha; Andri Soemitra; Zuhrinal M Nawawi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
Financial institutions that function as financial intermediaries on a smaller scale are known as microfinance institutions. However, there are microfinance institutions that do not operate in this way, especially those that do not accept deposits from individuals. because they are social institutions that provide microfinance. They use money from the Indonesian Amil Zakat Institute and empower people who live near the pesantren by giving them loans with different akd and low wages or profit-sharing ratio (only 3%). Micro Waqf Bank is the name given to microfinance institutions. The purpose of this study is to provide an explanation of the risk management design of Micro Waqf Banks and operating procedures for lending and financing.